Peningkatan Aktivitas Belajar Siswa Melalui Model Problem Based Learning Berbantuan Media Quiziz Pada Kelas V SDN Mlatiharjo 02 Semarang - Dewi Astuti; Choirul Huda; Anik Darminingsih; Rina Dwi Setyawati (Journal on Education, 2024)
This study intends to enhance student learning activities in mathematics classes V at SDN Mlatiharjo 02 Semarang by implementing the Problem Based Learning (PBL) learning model with assistance from Quizizz media. Data from student activity observation sheets were used in two cycles of this Classroom Action Research (CAR). According to the researcher's findings, there was a significant increase in student learning activities from pre-cycle to cycle II. In the pre-cycle, the average student activity percentage was 56.60%; in cycle I, it increased to 69.10%, and in cycle II, it reached 77.63%. This growth demonstrates how well the PBL model works with Quizizz to enhance student learning activities and increase their level of engagement, critical thinking, and activity participation.